2014
DOI: 10.1007/s10909-014-1144-2
|View full text |Cite
|
Sign up to set email alerts
|

A Quasiparticle Detector for Imaging Quantum Turbulence in Superfluid $$^3$$ 3 He-B

Abstract: We describe the development of a two-dimensional quasiparticle detector for use in visualising quantum turbulence in superfluid 3 He-B at ultra-low temperatures. The detector consists of a 5 × 5 matrix of pixels, each a 1 mm diameter hole in a copper block containing a miniature quartz tuning fork. The damping on each fork provides a measure of the local quasiparticle flux. The detector is illuminated by a beam of ballistic quasiparticles generated from a nearby black-body radiator. A comparison of the damping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…Further improvement is expected, if arrays of quartz tuning forks [6] or of resonators fabricated as micro-electromechanical systems (MEMS) become available as quasiparticle detectors. During the past decade it has been demonstrated that the zero temperature limit of 3 He-B can also be reached and explored in rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvement is expected, if arrays of quartz tuning forks [6] or of resonators fabricated as micro-electromechanical systems (MEMS) become available as quasiparticle detectors. During the past decade it has been demonstrated that the zero temperature limit of 3 He-B can also be reached and explored in rotation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently the ultra-low temperature regime of 3 He-B has moved in the forefront of general interest when it was realized that conventional sub-mK refrigeration techniques by means of adiabatic demagnetization cooling of copper are quite adequate if the total heat leak to the sample volume can be reduced to below ∼ 20 pW. This recognition has led to the development of new measuring techniques for the ballistic regime in superfluid 3 He which are based on the use of mechanical vibrating resonance devices [6] or the existence of a novel coherently precessing NMR mode [7]. Such work has been driven by the hope to reveal explicit new information on Andreev reflection, or on the existence of Andreev bound states on surfaces, interfaces, and vortex cores, or the expectation to identify the Majorana character in the spectrum of the bound state excitations [8].…”
Section: Introductionmentioning
confidence: 99%
“…With such a detector, we hope to make measurements similar to angleresolved photo-emission spectroscopy. For example, there are several potential sources of quasi-particles that produce a well-defined beam profile, such as black-body radiators [10,11]. The source could be used to illuminate a surface of the fluid with quasi-particles, while using the detector to measure the reflected flux.…”
Section: Introductionmentioning
confidence: 99%
“…The deviations in flux from that expected from a surface without bound states will tell us about the momentum transfer between bulk and surface states. The detector can also be used as a quasi-particle camera to image flow structures in 3 He, such as quantum turbulence [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tuning forks are nowadays widely exploited in helium low temperature experiments as thermometers, viscometers, pressure sensors, turbulence detectors, etc. 13,14 In our measurement scheme resembling the so-called near-field acoustic microscopy, 15,16 an oscillating quartz tuning fork is placed in the vicinity of the surface of the solid. A change in the distance z between the interface and the fork distorts the velocity field in the liquid around the oscillating fork and thus changes its effective hydrodynamic mass.…”
mentioning
confidence: 99%